PRAKTEK BUDAYA MERARIQ DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus Desa Tibu Sisok Kecamatan Janapria Kabupaten Lombok Tengah) - Syaiful Anwar; Nur Hasan; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
The Sasak people recognize Merariq as a culture that initiates marriage, not applying for a girl through her guardian. Marry ran a secret meeting with the girl and took her away at night to a hiding place. The bridegroom sneaks out of his parents' house as planned and the groom is usually escorted by his family or close friends. In some cases, the bride stays in her house and instructs the trustee to kidnap the woman in question for her. This kidnapping is considered successful if the prospective bride and groom hide themselves in a secret place (usually infiltrating), usually at the home of one of the prospective patriletral relatives of the bridegroom. Based on this context, the main problem of this research is how to practice merariq culture in the perspective of Islamic law. And based on the main subject matter, the focus of this research is about the merariq cultural practices that exist in Lombok, the views of religious leaders and traditional leaders about merariq culture, and the views of Islamic law about merariq culture. In this study researchers used empirical and juridical syar'i sociological approaches and qualitative descriptive types. Kata Kunci : Praktek Merariq, Perspektif, Hukum Islam